Mini-open Muscle Resection Procedure under Local Anesthesia for Lateral and Medial Epicondylitis - Cho, Byung-Ki (The Korean Orthopaedic Association, 2009)
BACKGROUND: This study examined the clinical results of surgical treatment using a mini-open muscle resection procedure under local anesthesia for intractable lateral or medial epicondylitis. METHODS: Forty two elbows (41 patients) were treated surgically for lateral or medial epicondylitis. The indication for surgery was refractory pain after six months of conservative treatment, or a history of more than three local injections of steroid, or severe functional impairment in the occupational activities. The treatment results were assessed in terms of the pain using the visual analogue scale (VAS), Roles & Maudsley score, and Nirschl & Pettrone grade. RESULTS: The preoperative VAS scores of pain were an average of 5.36 at rest, 6.44 at daily activities, and 8.2 at sports or occupational activities. After surgery, the VAS scores improved significantly (p < 0.01): 0.3 at rest, 1.46 at daily activities, and 2.21 at sports or occupational activities. The preoperative Roles & Maudsley score was acceptable in 6 cases, and poor in 36 cases, which was changed to excellent in 23 cases, good in 16 cases, acceptable in 3 cases after surgery. According to the grading system by Nirschl & Pettrone, 23 cases were excellent, 18 cases were good, and the remaining 1 case was fair. Overall, 41 cases (97.6%) achieved satisfactory results. Postoperative complications were encountered in three cases. Subcutaneous seroma due to the leakage of joint fluid in two patients was managed by additional surgery and suction drainage, and resulted in a satisfactory outcome. One patient complained of continuous pain on occupational activity, but her pain at rest was improved greatly. CONCLUSIONS: The mini-open muscle resection procedure under local anesthesia appears to be one of effective methods for intractable lateral or medial epicondylitis.